ANALYSIS OF FACTORS AFFECTING THE PARTICIPATION RATE IN INDONESIA SENIOR HIGH SCHOOL - Siti Nurjanah (Jurnal Ilmiah Econosains, 2019)
This study aimed to determine the effect of Fiscal Decentralization, Government Expenditure on Education, the GDRP per capita, a ratio of students per teacher and the Gross Participation Rate on Senior High School in Indonesia. The type of data using secondary data on local revenues, total revenues, the ratio of government expenditure on education to total government expenditure, the number of students, number of teachers, and the gross participation rate. Data were analyzed using panel data regression analysis. The results showed that government expenditure on education, the ratio of students per teacher and the number of teachers has a significant positive effect on secondary school gross participation rate in Indonesia.